Redefinition and taxonomic revision of the "buqueti" species-group, Dichotomius Hope, 1838 (Coleoptera: Scarabaeidae: Scarabaeinae) - Arias-Buriticá,Jorge Armando (2019)
ABSTRACT On the basis of external morphology and genitalia of males, as well as a comparison between different species belonging to other groups of Dichotomius, we propose a redefinition of the "buqueti" species group separated by Luederwaldt (1929). Six species are excluded from this group and transferred to other groups: D. ribeiroi (Pereira, 1954) in the "cotopaxi" group; D. camposeabraiMartínez, 1974 in the "bitiensis" group; D. reclinatus (Felsche, 1901), D. horridus (Felsche, 1911), D. quadrinodosus (Felsche, 1901) and D. nimuendaju (Luederwaldt, 1925) (revalidated species) forming the newly defined "reclinatus" group. The other species kept in the "buqueti" group include D. buqueti (Lucas, 1857) from Brazil (lectotype here designated), D. haroldi (Waterhouse, 1891) from Argentina and D. nutans (Harold, 1867) from Brazil, Argentina and Uruguay. The taxonomic revision of the "buqueti" group are presented, including a history of the included species, a determination key, illustrations of the structures of external morphology, male genitalia and sclerites of the internal sac, and a distribution map.